TRANSFORMATIONAL LEADERSHIP OF THE PRINCIPAL AS AN EFFORT TO REALIZE THE VISION AT SMPIT NUR HIDAYAH SURAKARTA - Amara Nairani Safhira; Istanto (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
The principal’s leadership plays a crucial role in determining the direction and success of schools in realizing their vision and mission. In the context of integrated Islamic education, transformational leadership is particularly relevant as it emphasizes role modeling, motivation, innovation, and individualized attention to mobilize all school members. This study aims to examine how transformational leadership is practically enacted by the principal in realizing the vision of SMPIT Nur Hidayah Surakarta (Nur Hidayah Surakarta Integrated Islamic Junior High School), namely “To create an Islamic generation with strong character, high achievement, and leadership qualities.” This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the school principal and the vice principal of curriculum, observations, and documentation. The data were analyzed using Miles and Huberman’s interactive model, consisting of data condensation, data display, and conclusion drawing/verification. The findings reveal that the principal consistently implements the four dimensions of transformational leadership. Idealized influence is reflected in exemplary behavior and a strong commitment to Islamic values; inspirational motivation is demonstrated through spiritual motivation and the consistent internalization of the school vision; intellectual stimulation is realized through educational innovations such as ICT-based classes, digitalization of school information systems, bilingual programs, and community empowerment initiatives; while individualized consideration is shown through personal attention, spiritual guidance, and systematic teacher professional development through workshops. The novelty of this study lies in its detailed analysis of how the four dimensions of transformational leadership are concretely implemented to internalize the school vision within an integrated Islamic junior high school context. This study contributes theoretically to transformational leadership studies in Islamic education and practically provides insights for school leaders in translating vision into sustained educational practices.